DEVELOPING HOPSCOTCH BOARD FOR LEARNING READING OF DESCRIPTIVE TEXT IN JUNIOR HIGH SCHOOL - Lutfi Nuraini Ismaiyah; Dian Fadhilawati (Universitas Islam Balitar, 2022)
The aims of this research are to develop a hopscotch board for learning reading of a descriptive text in junior high schools, know the validity of the developed hopscotch board for learning reading of the descriptive text, and gain the teachers’ and students’ responses toward the developed hopscotch board for learning reading of the descriptive text. This research adapted Research and Development (R&D) design based on Sugiyono’s model, which includes: (1) Finding potential and problem solution; (2) Design and development; (3) Experts validation and revision; (4) Teachers’ and students’ responses; (5) Evaluation by experts and revision; and (6) Final product. The findings revealed that: (1) the model of developed hopscotch board for learning reading descriptive text consisted of a hopscotch board, markers, ownership signs, how to play (for one group instruction and more than one group instruction), cards (reading descriptive cards, exercise cards, a key answer of exercise cards, punishment cards, and key answer of punishment cards), and 2 guidebooks (for teacher and students). (2) The developed hopscotch board was valid, it was proved by the result of material experts’ validation of 95% (very valid), and media experts’ validation of 95% (very valid). Furthermore, (3) Students and teachers gave positive responses toward the developed hopscotch board as learning media for learning to read the descriptive text as reflected in the result of the questionnaire given in which got 89% (very good) from students and 90% (very good) from the teachers. From the result above, we can infer that the developed hopscotch board was valid and appropriate to be used as an alternative media for learning reading of the descriptive text in junior high schools.